1997
DOI: 10.1074/jbc.272.23.15023
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Proliferation in Response to Interleukins 2 and 7 Requires p38MAP Kinase Activation

Abstract: Interleukin-2 (IL-2) is a potent T cell mitogen. However, the signaling pathways by which IL-2 mediates its mitogenic effect are not fully understood. One of the members of the mitogen-activated protein kinase (MAPK) family, p42/44MAPK (ERK2/1), is known to be activated by IL-2. We have now investigated the response to IL-2 of two other members of the MAP kinase family, p54MAP kinase (stress-activated protein kinase (SAPK)/Jun-N-terminal kinase (JNK)) and p38MAP kinase (p38/Mpk2/CSBP/RK), which respond primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(146 citation statements)
references
References 64 publications
8
133
3
Order By: Relevance
“…1). In contrast to the above data, 20:4 6 did not enhance p38 dual phosphorylation in Jurkat cells (data not shown) that express p38 (26).…”
Section: Resultscontrasting
confidence: 52%
“…1). In contrast to the above data, 20:4 6 did not enhance p38 dual phosphorylation in Jurkat cells (data not shown) that express p38 (26).…”
Section: Resultscontrasting
confidence: 52%
“…One such compound, SB203580, blocks the activity of p38␣ and p38␤, but does not inhibit p38␥ and p38␦ (23), nor the extracellular signal-related kinases or c-Jun N-terminal kinases (24,25). It has been reported that the production of IFN-␥ by T cells, following activation by specific Ag-pulsed APC, is mediated by the p38 MAPK signaling pathway (26).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in the mesenteric lymph nodes, where pre-matured T cells expand and mature into cytotoxic T cells, donor-derived CD8 + and CD4 + lymphocytes are fewer in p38a +/--grafted mice. Several studies have reported that activated p38 up-regulates the expression of several cytokines, such as IL-12p40, IL-18, and IL-4 [16,17,27], and plays essential roles in T cell proliferation in vitro and in vivo [18][19][20]. The induction of Th1-dominant cytokines, such as IL-12p40 and IL-18, was suppressed in the MLNL of p38a +/--grafted mice, which may be one of the reasons why fewer lymphocytes infiltrated into the MLNL.…”
Section: Discussionmentioning
confidence: 99%
“…Among the four mammalian isoforms of p38 (p38a, -b, -c, and -d), p38a is expressed relatively ubiquitously [10][11][12], and p38a-deficient mice have been reported to be homozygous embryonic lethal due to either abnormal erythropoiesis or placental organogenesis [13]. The p38 plays a pivotal role in Th1/Th2 responses by regulating the expression of cytokines, such as IL-2, IL-4, IL-12, and IFN-c [14][15][16][17], and also plays important roles in modulating proliferation and cell death [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%